2016
DOI: 10.1088/1752-7155/10/3/037101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of microbiome-related confounding factors on the reproducibility of the volatolomic test

Abstract: Volatile organic compound (VOC) testing in breath has potential in gastric cancer (GC) detection. Our objective was to assess the reproducibility of VOCs in GC, and the effects of conditions modifying gut microbiome on the test results. Ten patients with GC were sampled for VOC over three consecutive days; 17 patients were sampled before and after H. pylori eradication therapy combined with a yeast probiotic; 61 patients were sampled before and after bowel cleansing (interventions affecting the microbiome). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
(58 reference statements)
0
20
0
Order By: Relevance
“…Two further studies highlighted the correlation between VOCs and gastric cancer (GC). Leja et al [21] demonstrated that although VOCs measurements were well reproducible in GC patients, and specific modifications of the intestinal microbiome may have influenced the VOC results. The authors concluded that gastrointestinal interventions, including the use of antibiotics in Helicobacter pylori eradication and bowel cleansing for colonoscopy, could potentially affect the diagnostic accuracy of breath VOCs.…”
Section: Resultsmentioning
confidence: 99%
“…Two further studies highlighted the correlation between VOCs and gastric cancer (GC). Leja et al [21] demonstrated that although VOCs measurements were well reproducible in GC patients, and specific modifications of the intestinal microbiome may have influenced the VOC results. The authors concluded that gastrointestinal interventions, including the use of antibiotics in Helicobacter pylori eradication and bowel cleansing for colonoscopy, could potentially affect the diagnostic accuracy of breath VOCs.…”
Section: Resultsmentioning
confidence: 99%
“…Storing and sampling conditions impairing gut microbiome preservation potentially have a significant influence on fecal VOC composition as well. The significant effect of the microbiome on the volatolome is well illustrated in a recently published study demonstrating that interventions with a significant effect on the gut microbiome, such as bowel cleansing and administration of antibiotics in Helicobacter pylori eradication therapy, have a significant effect on detected volatiles [33]. In addition, fecal VOC profiles from patients with a gastrointestinal Clostridium difficile infection exhibit a significant different volatile profile compared to non-infected controls [34,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Especially when aiming to find a novel non-invasive biomarker to prevent the performance of (unnecessary) endoscopic assessment of pediatric patients, it is important to include a realistic selection of patients with gastro-intestinal symptoms representing clinical practice, since this is the population that would potentially gain the most from an alternative diagnostic biomarker. In addition we included de novo IBD patients, circumventing bias by VOC altering effects of bowel lavage and immunosuppressive medication [34]. All controls were successfully matched to a case based on age and gender.…”
Section: Discussionmentioning
confidence: 99%